Diffusion-affected charge transfer: demonstration experiment for the linear relationship between current and its semiintegral - Tamás Pajkossy (Electrochemistry Communications)
Diffusion-affected charge transfer is a basic situation of electrochemical kinetics; the rate coefficients are often estimated by analyzing cyclic voltammograms. Provided that a couple of conditions hold, decoupling of diffusion and charge transfer is possible by using a recent theory leading to a linear relation of the current and its so-called semiintegral. Accordingly, a set of voltammograms of such reactions, measured with varied scan rates, can be transformed into two functions characteristic of charge transfer and diffusion separately, yielding charge transfer rate coefficients. We present here voltammograms measured on a well-known electrochemical system (gold electrode in a ferrocyanide/ferricyanide containing aqueous solution) and demonstrate the applicability of the above-mentioned linear relation; finally, we calculate the charge transfer rate coefficients as a function of the electrode potential. The main advantages and disadvantages of the analysis method are discussed, along with the limitations of the practical applicability.